(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the status of treatment adherence and some related factors in patients with type 2 diabetes at Thuy Nguyen District Health Center, Hai Phong, in 2022 Research method: An analytical cross-sectional study was performed on 245 patients. Results: The majority of patients were prescribed oral drugs at 78.8%, and the rate of using 2 drugs in combination was the highest at 46.9%. The overall adherence rate was 15.9%. Some factors related with statistical significance to general adherence to treatment for type 2 diabetes: the rate of adherence to drug use in the treatment of women is 2.22 times higher than that of men (p<0.05); Education level related to dietary adherence in patients with type 2 diabetes (p<0.05). Conclusion: The rate of treatment adherence of patients with type 2 diabetes is still low, showing that the degree of non-compliance with treatment regimens is a worrying fact. Therefore, health center health workers need to strengthen counseling and guidance for patients and their families on nutrition, physical activity, and self-control of blood sugar at home, and gradually increase the rate of diabetes, overall compliance, contributing to limiting complications, and mortality, and improving the quality of life for patients with type 2 diabetes